2017
DOI: 10.5430/rwe.v8n2p59
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Health Expenditure on Economic Development – Evidence from Prefecture-Level Panel Data of Shandong Province

Abstract: Public health expenditure is an indispensable part of social economy. The public has always paid close attention to public health expenditure. In order to study the quantitative relation between public health expenditure and social economic development, this paper investigates prefecture-level cities in Shandong Province, due to the unique characteristics of Shandong Province. Making theoretical and empirical contributions, this paper augments the Cobb-Douglas production function with public health expenditure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
2
1
0
Order By: Relevance
“…Enhancing the public health expenses increases economic development. The research findings showed consistent results with ( 19 , 20 , 50 ). At the same time, there is a negative but statistical association between renewable energy and the economy's Gross domestic product.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Enhancing the public health expenses increases economic development. The research findings showed consistent results with ( 19 , 20 , 50 ). At the same time, there is a negative but statistical association between renewable energy and the economy's Gross domestic product.…”
Section: Resultssupporting
confidence: 83%
“…The findings of the research were consistent with ( 19 , 47 , 50 , 51 ). First increasing the expenditure on public health will help in boosting the performance of the economy.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 86%
See 1 more Smart Citation